2008
DOI: 10.1089/jamp.2007.0634
|View full text |Cite
|
Sign up to set email alerts
|

Handling of and Preferences for Available Dry Powder Inhaler Systems by Patients with Asthma and COPD

Abstract: The correct handling of dry powder inhalers (DPIs) is crucial for efficient therapy, and acceptance of the device can improve compliance. The handling of seven different dry powder inhalers was studied in 72 patients with asthma and chronic obstructive pulmonary disease (COPD). The aim of this study was to identify possible handling errors and investigate patient preferences. Patients inhaled twice with each inhaler; first after reading the device leaflet, and second after device handling was explained by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 8 publications
3
74
0
2
Order By: Relevance
“…Among the preferred ways of inhaler training were demonstration (56.3%), video (19%), and brochures and leaflets (18%) (16). The studies concerned have showed that correct device handling has to a large extent improved the therapeutic outcomes (17).…”
Section: Other Errors Related With Dry Powder Inhalersmentioning
confidence: 99%
“…Among the preferred ways of inhaler training were demonstration (56.3%), video (19%), and brochures and leaflets (18%) (16). The studies concerned have showed that correct device handling has to a large extent improved the therapeutic outcomes (17).…”
Section: Other Errors Related With Dry Powder Inhalersmentioning
confidence: 99%
“…In turn, devices associated with the lowest numbers of handling errors have the highest patient preference ratings [12,13], suggesting that a patient’s acceptance of a device may be correlated with ease of handling. Therefore, device handling, correct inhaler technique, patient preference, and adherence are intertwined factors that all contribute to good symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the patients' skill in the device practicality, as well as their knowledge of the operational manoeuvres consenting the proper and effective inhalation of the drug emitted are inadequate [13]. As a consequence, the causes of patients' incorrect inhalation procedures and the determinants of patients' preference and acceptance had been extensively investigated, mainly being the patient's confidence and beliefs highly valued and regarded as the very crucial steps of the process to improve [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the determinants of patients' incorrect inhalation procedures [7,8] and those of patients' preference, acceptance, and satisfaction focused the attention of the majority of researchers [9][10][11][12][13][14][15]. The primary role of patients' viewpoint was then highly valued in recent years, even if the attempts to quantify objectively the correspondence between patients' beliefs and real usability in real life by means of specific instruments were only episodically pursued [11,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%